A structurally enriched agricultural landscape maintains high reptile diversity in sub‐arid south‐western Madagascar. Issue 2 (17th August 2016) - Nopper, Joachim; Lauströer, Balten; Rödel, Mark‐Oliver; Ganzhorn, Jörg U.
Summary: The concept of biodiversity conservation relies primarily on protected areas. Yet, protected areas are influenced by the surrounding anthropogenic matrix as degradation of landscapes used by humans also has negative consequences on species within the adjacent protected, non‐degraded ecosystems. Increasing the heterogeneity of the anthropogenic landscape has the potential to promote biodiversity conservation in protected and non‐protected sites. To find options for reconciling land use and biodiversity conservation, we evaluated reptile diversity of two areas. Both areas contained three types of habitat: cultivated areas, degraded forest and undegraded forest. In one area ( Tsim ), a network of hedges surrounding fields provided a variety of possible resources for reptile species. Another area ( Andremba ) lacked such landscape elements. In 480 survey walks on 48 transects evenly distributed over two areas, we recorded a total of 24 reptile species, of which 18 occurred in both areas. Perennial plant cover explained the variation in local (per transect) species richness best. Species richness was low along field margins in the cultivated area that lacked hedges and had a perennial plant cover below 20%. It was high in undegraded and degraded forest and along hedges in the cultivated area where perennial plant cover was above 40%. Similarities of reptile assemblages were higher between habitat types in the area structurally enriched with hedges, than in the area lacking such enrichment. In the latter area, beta diversity was largely the result of species losses which could result from impeded movement between habitats. Synthesis and applications . A continuous network of hedges and associated trees and shrubs contribute to the maintenance of reptile biodiversity in dry south‐western Madagascar. When present, these interconnected landscape elements enhance habitat suitability of the agriculturally used matrix. They also provide habitat for species of conservation concern. High similarity between assemblages in the area with hedges indicated that movement between habitats was facilitated. We conclude that incorporating hedges in pastures contributes not just to the suitability of the matrix, but also enhances landscape connectivity and thus improves biodiversity conservation in the human‐used landscape.